2018
DOI: 10.3390/atmos9080299
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nonlocal Vehicle Restriction Policy on Air Quality in Shanghai

Abstract: Abstract:In recent years, road space rationing policies have been increasingly applied as a traffic management solution to tackle congestion and traffic emission problems in big cities. Existing studies on the effect of traffic policy on air quality have mainly focused on the odd-even day traffic restriction policy or one-day-per-week restriction policy. There are few studies paying attention to the effect of nonlocal license plate restrictions on air quality in Shanghai. Restrictions toward nonlocal vehicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In the meantime, the policies are various in restrict scopes and guidelines as in Table 1 , which not only causes inconvenience to local residents, but also causes great trouble to vehicles from other cities [ 38 ]. Traffic delay and emissions have a strong connection, which means that reducing delay could reduce emissions [ 39 , 40 , 41 ]. Different route selections and stop strategies could reduce bus emissions [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, the policies are various in restrict scopes and guidelines as in Table 1 , which not only causes inconvenience to local residents, but also causes great trouble to vehicles from other cities [ 38 ]. Traffic delay and emissions have a strong connection, which means that reducing delay could reduce emissions [ 39 , 40 , 41 ]. Different route selections and stop strategies could reduce bus emissions [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…• Polynomial regression is applied to evaluate the general trend in the air pollution concentration or levels of noise with and without the implementation of the road traffic restrictions in Madrid Central. Although is one of the simplest methods for analysis and estimation of time series, yet it is frequently used in the related literature [12,35,38] In this article, two polynomial regression methods are studied: linear and polynomial of grade 10.…”
Section: Methodsmentioning
confidence: 99%
“…Overall, authors found positive effects on the improvement of public health. More research had been performed addressing the LEZ analysis in China [36][37][38].…”
Section: Related Workmentioning
confidence: 99%
“…Overall, the authors found positive effects on the improvement of public health. More research had been performed addressing the LEZ analysis in China [36][37][38].…”
Section: Related Workmentioning
confidence: 99%
“…Polynomial regression is applied to evaluate the general trend in air pollution concentration or levels of noise with and without the implementation of the road traffic restrictions in Madrid Central. While it is one of the simplest methods for analysis and estimation of time series, it is frequently used in the related literature [12,35,38] In this article, two polynomial regression methods are studied: Linear and polynomial of grade 10.…”
mentioning
confidence: 99%